Pendidikan Multikultural dalam Al-Quran dan Hadits - Yaqin, M. Ainul; Maksum, Muh Nur Rochim (MODELING: Jurnal Program Studi PGMI, 2023)
Religious plurality anywhere in the world, except for certain places, is a reality that cannot be denied. Contacts between communities of different cultures are increasing. Indonesia is known as a pluralistic society, this can be seen from the existing social reality. Evidence of its plurality can also be proven through the motto Bhinneka Tunggal Ika. multicultural education is a solution to calm as well as a solution to education in Indonesia. This work was compiled based on data in the form of library research with a philological-phenomenological approach. From this study, it was found that the values of multicultural education can be found in the Qur'an and Hadith and can be implemented by implementing several things such as building an inclusive religious paradigm in the school environment, respecting language diversity in schools, building gender sensitive attitudes in schools, building critical understanding of social differences, building anti-ethnic discrimination attitudes, respecting differences in abilities, and respecting age differences.